Avaliação clínica e histológica de osteonecrose mandibular induzida por agentes modificadores ósseos em ratos wistar - Silva, Luisa Berlato (2021)
Osteonecrosis is a bone pathology, with a still unknown etiopathogenesis, which was first reported in 2003 by Marx. In 2014 the Association of Oral and Maxillofacial Surgeons (AAOMS) described the concept of osteonecrosis, as an area of bone exposure in the jaw or jaw that does not repair in eight weeks due to a temporary or permanent loss of blood supply at the site. It affects, in most cases, patients who chronically use antiresorptive drugs and some associated factors such as corticosteroid therapy, diabetes mellitus, tooth extraction and other invasive dental procedures. Recent work investigates in rats the osteonecrosis induced by these drugs, such as alendronate (AL), zoledronic acid (Z) and denosumab (Dmab), in order to clarify the etiopathogenesis, as well as to study means of prevention and treatment of the disease. the aim of this study was to compare antiresorptive drugs in an animal model in MRONJ rats, using three different antiresorptive drugs: alendronate, zoledronic acid and denosumab, one for each experimental group, based on the clinical and histological parameters of the region undergoing extraction. The clinical parameters evaluated were: area of bone exposure, fistula, poor healing of soft tissue and inflammation in the alveolus. The histological parameters included the analysis of bone necrosis, inflammatory infiltrate (qualitative and quantitative analysis), blood vessels (quantitative analysis), bone sequestration and root rest. There were 35 male Wistar rats, randomized into 6 groups: Negative Control Group (CN) physiological saline therapy: GNZ (n = 6), GNAL (n = 6), GNDmab (n = 5); Alendronate Group (GAL) therapy with AL (n = 6); Zometa Group (GZ) Z therapy (n = 6); Denosumab Group (GDmab) Dmab therapy (n = 6). The dose applied to each animal will be according to its weekly weight, following the ratio: GAL 1 mg / Kg - subcutaneous, GZ 0.06mg / kgintraperitoneal and GDmab 0.25mg / kg - intraperitoneal. The GAL group was submitted to 8 applications of LA for a period of 8 weeks (1 weekly application), when completing the eighth week the rats were submitted to tooth extraction. And after 28 days of tooth extraction, they were euthanized, along with 6 rats from the GNAL group. The medication was maintained, once a week, until euthanasia (thirteenth week) for the GAL group. The GZ group received Z four times a week, for four weeks, when the fourth week was completed, tooth extraction was performed, after which the 28-day period was awaited for the euthanasia of the animals in the respective group and another 6 in the GNZ group. The GDmab group received a total of 8 applications of Dmab, for a period of 4 weeks (2 weekly applications), when the fourth week was completed, the animals in the group underwent dental extraction and after 28 days were euthanized, together with the 6 remaining rats from the GNDmab group. The statistical analysis for qualitative variables was used Fisher's exact test, and for the analysis of quantitative variables, One-way ANOVA with Tukey's post hoc was used. Considering a significance level of 0.05. Our results demonstrated a higher prevalence of histological osteonecrosis in the group in the BFs when compared to the Denosumab group, as well as the decrease in the number of vessels was more frequent in the groups of the BFs. Thus, we conclude that, due to the decrease in angiogenesis and the increase in MRONJ in bone tissue, bisphosphonates have a greater alteration in the bone mechan